2018
DOI: 10.3390/nu10020178
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Dietary Energy Density among Preschool Aged Children

Abstract: Childhood obesity is a global problem with many contributing factors including dietary energy density (DED). This paper aims to investigate potential predictors of DED among preschool aged children in Victoria, Australia. Secondary analysis of longitudinal data for 209 mother–child pairs from the Melbourne Infant Feeding, Activity and Nutrition Trial was conducted. Data for predictors (maternal child feeding and nutrition knowledge, maternal dietary intake, home food availability, socioeconomic status) were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
(74 reference statements)
1
11
0
1
Order By: Relevance
“…Total energy and nutrient intake were calculated as individual means of the three recorded days. Dietary energy density (DED) was calculated excluding non-caloric beverages according to [46]. Protein intake was expressed as g/kg BW and fiber intake as g/1,000 kcal.…”
Section: Methodsmentioning
confidence: 99%
“…Total energy and nutrient intake were calculated as individual means of the three recorded days. Dietary energy density (DED) was calculated excluding non-caloric beverages according to [46]. Protein intake was expressed as g/kg BW and fiber intake as g/1,000 kcal.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the substitution of ≥2 servings fresh fruit for higher ED snacks or desserts typical in Western diets can help to reduce total dietary ED to <1.75 kcal/g needed to better support weight control or promote modest weight loss. Providing fresh fruit early in a child’s life is one of the best healthful eating behaviors that is predictive of lower energy intake later in life [133]. A cross-sectional study of weight loss maintainers who lost >10% of their body weight and maintained that loss for ≥5 years reported that they consumed diets with ≤1.4 kcal/g compared to those with weight re-gain who consumed a diet with ≥1.8 kcal/g [134].…”
Section: Emerging Health Benefits Associated With Whole Fruits Andmentioning
confidence: 99%
“…All regression models were adjusted for the following covariates: child's sex, child's age at time of HFA data collection, mother's age at baseline, mother's education, mother's employment, child's ethnicity and number of individuals in household. These covariates were selected a priori based on previous studies of HFA and diet in children between 18 and 36 months of age (Bryant et al, 2011;Collins, Lacy, Campbell, & McNaughton, 2016;Fernando, Campbell, McNaughton, Zheng, & Lacy, 2018). Models examining prospective associations were additionally adjusted for the child's age at the time of outcome assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Only two previous studies, both conducted using data from the Melbourne Infant Feeding, Activity and Nutrition Trial in Australia, have explored the relationship between HFA during the first 1000 days and later dietary intake, but neither examined HFA quantities. They found that having snack foods in the home more frequently at 18 months of age was associated with greater overall dietary energy density at 3.5 years of age (Fernando, Campbell, McNaughton, Zheng, & Lacy, 2018) and that increased frequency of having fruits available in the home was linked to a lower overall dietary energy density (Fernando, Campbell Public Health England, 2019). Additionally, serving sizes for 1-to 3-year-olds are approximately a quarter of those for adults (American Academy of Pediatrics: Committee on Nutrition, 2016), with one serving equalling one half to two biscuits (6-23 g) or 100-120 ml of SSBs (Infant and Toddler Forum, 2014).…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation